Waixenicin A, a marine-derived TRPM7 inhibitor: a promising CNS drug lead - Sun Hong-Shuo; Horgen F. David; Romo Daniel; Hull Kenneth G.; Kiledal Sigrid A.; Fleig Andrea; Feng Zhong-Ping (Acta Pharmacologica Sinica; Vol 41, No 12 (December 2020): Acta Pharmacologica Sinica, 2020)
Ion channels are the third largest class of targets for therapeutic drugs. The pharmacology of ion channels is an important research area for identifying new treatment options for human diseases. The past decade or so has seen increasing interest in an ion channel protein belonging to the transient receptor potential (TRP) family, namely the melastatin subfamily member 7 (TRPM7), as an emerging drug target. TRPM7 is a bifunctional protein with a magnesium and calcium-conducting divalent ion channel fused with an active kinase domain. TRPM7 is ubiquitously expressed in human tissues, including the brain, and regulates various cell biology processes such as magnesium and calcium homeostasis, cell growth and proliferation, and embryonic development. TRPM7 provides a link between cellular metabolic status and intracellular calcium homeostasis in neurons due to TRPM7’s unique sensitivity to fluctuating intracellular Mg·ATP levels. Thus, the protein plays a key role in ischemic and hypoxic neuronal cell death and brain injury, and is one of the key nonglutamate mechanisms in cerebral ischemia and stroke. Currently, the most potent and specific TRPM7 inhibitor is waixenicin A, a xenicane diterpenoid from the Hawaiian soft coral Sarcothelia edmondsoni. Using waixenicin A as a pharmacological tool, we demonstrated that TRPM7 is involved in promoting neurite outgrowth in vitro. Most recently, we found that waixenicin A reduced hypoxic–ischemic brain injury and preserved long-term behavioral outcomes in mouse neonates. We here suggest that TRPM7 is an emerging drug target for CNS diseases and disorders, and waixenicin A is a viable drug lead for these disorders.